Pengembangan Model Boost-Buck untuk Mempertinggi Stabilitas Tegangan Keluaran Konverter DC-ke-DC - Freddy Kurniawan (Jurnal EECCIS, 2018)
Abstract— This paper presented a novel boost-buck converter to provide the DC-DC converter. The converter consists of a cascaded configuration of the boost and buck converter. The boost converter supplied the voltage for the buck converter by converting the input voltage to the shared capacitor voltage with four modes operation: idle, up-transient, boost, and down transient. Meanwhile, the buck converter converted the shared capacitor voltage to the output voltage. To provide the fast-transient and low- ripple output-voltage, the buck converter responded the overshoot or undershoot of the output voltage by directly increasing or decreasing the on/off time of switching pulse. As the results, the transient response can be reduced to 1μs and the ripple output-voltage can be improved to 20 mV for the 5 A load current.Key Words — DC-DC Converter, Boost-buck, Fast- transient, Low-rippleAbstrak— Pada artikel ini dibahas model boost-buckuntuk membentuk konverter DC-ke-DC. Konverter ini tersusun dari konverter boost dan buck. Konverter boost mengonversi tegangan masukan menjadi tegangan di kapasitor bersama dengan empat mode operasi: tanpa beban, transisi-naik, boost, dan transisi-turun. Sementara itu konverter buck mengonversi tegangan di kapasitor bersama menjadi tegangan keluaran. Untuk memperkecil waktu transien dan tegangan kerut, konverter buck menanggapi kemungkinan naik/turunnya tegangan keluaran dengan manurunkan/menaikkan waktu on/off pulsa switching. Konverter boost-buck ini mempunyai waktu transien 1 mikrodetik dan tegangan kerut 20 mV pada beban 5 A.Kata Kunci— Konverter DC-ke-DC, Boost-buck, waktu transien, tegangan kerut.